Lasting impairments following transient ischemic attack and minor stroke: a systematic review protocol - Hede Ebbesen, Birgitte; Modrau, Boris; Kontou, Eirini; Finch, Emma; Crowfoot, Gary; Crow, Jennifer; Heron, Neil; Hodson, Tenelle; Skrubbeltrang, Conni; Turner, Grace (Frontiers in Neurology, 2023)
Introduction The focus on medical management and secondary prevention following Transient Ischemic Attack (TIA) and minor stroke is well-established. Evidence is emerging that people with TIA and minor stroke can experience lasting impairments as fatigue, depression, anxiety, cognitive impairment, and communication difficulties. These impairments are often underrecognized and inconsistently treated. Research in this area is developing rapidly and an updated systematic review is required to evaluate new evidence as it emerges. This living systematic review aims to describe the prevalence of lasting impairments and how they affect the lives of people with TIA and minor stroke. Furthermore, we will explore whether there are differences in impairments experienced by people with TIA compared to minor stroke. Methods Systematic searches of PubMed, EMBASE, CINAHL, PsycINFO, Cochrane Libraries will be undertaken. The protocol will follow the Cochrane living systematic review guideline with an update annually. A team of interdisciplinary reviewers will independently screen search results, identify relevant studies based on the defined criteria, conduct quality assessments, and extract data. This systematic review will include quantitative studies on people with TIA and/or minor stroke that report on outcomes in relation to fatigue, cognitive and communication impairments, depression, anxiety, quality of life, return to work/education, or social participation. Where possible, findings will be grouped for TIA and minor stroke and collated according to the time that follow-up occurred (short-term < 3 months, medium-term 3–12 months, and long-term > 12 months). Sub-group analysis on TIA and minor stroke will be performed based on results from the included studies. Data from individual studies will be pooled to perform meta-analysis where possible. Reporting will follow the Preferred Reporting Items for Systematic review and Meta-Analysis Protocol (PRISMA-P) guideline. Perspectives This living systematic review will collate the latest knowledge on lasting impairments and how these affect the lives of people with TIA and minor stroke. It will seek to guide and support future research on impairments emphasizing distinctions between TIA and minor stroke. Finally, this evidence will allow healthcare professionals to improve follow-up care for people with TIA and minor stroke by supporting them to identify and address lasting impairments.